Performance improvement studies of masonry houses using elastic post-tensioning straps. - Turer, Ahmet
Unreinforced masonry houses are composed of building blocks with weak inter-binding action between them which commonly possess low tensile strength. The principal tensile stresses generated by out-of-plane bending and in-plane shear forces cannot be tolerated well and leads to heavy structural damage and brittle collapse beyond linear capacity of the material. Remedies such as externally applied mesh reinforcement and post-tensioning improves post and pre-cracking performances; however, yielding of reinforcement material or shortening of walls due to cracking causes loss of integrity and post-tensioning force. This paper discusses a research programme on earthquake strengthening of masonry houses using post-tensioning by elastomeric straps and related shaking table tests on 1/10 scale single storey rural dwelling models. The aim of the study is to assess the use and effectiveness of post-tensioning rubber straps at several different configurations especially for houses with heavy earth roofs supported on wooden logs. Full-scale application can be conducted using scrap automobile tyres, which might be implemented as an economic and environment friendly alternative strengthening technique for poor residents of low-cost dwellings. The performance and validity of the proposed strengthening techniques were tested on 1/10 scale models using a simplistic shaking table. The structural performance of the reinforced models with vertical post-tensioning rubber straps was significantly improved as compared to the original specimen; the results were even better when vertical and horizontal straps were used. Obtained results show promise for seismic strengthening using rubber straps for post-tensioning.
Keywords: Masonry; Earthquake; Seismic; Strengthening; Rubber